Analysis of leprosy cases in the state of Pará between 2001 and 2020 - Alves Silva, Lyncoln Eduardo (2024)
Background and Objectives: leprosy is a mycobacteriosis known for centuries and prevalent to this day and, despite the reduction in the number of cases, it still affects many Brazilians. To this end, this study aimed to assess the clinical forms of leprosy in the state of Pará between 2001 and 2020. Methods: an ecological study was carried out using data from the Notifiable Diseases Information System (SINAN) of patients with leprosy according to three classifications, such as notified clinical form, notified operational classification and notified grade of disability, collected between 2001 and 2020. Results: the milder forms of leprosy had a greater decrease than the more severe form, combined with a greater drop in cases in the paucibacillary class compared to the multibacillary classification. Furthermore, grade zero disability showed a large reduction in cases, in contrast to grades one and two, which remained stationary. Conclusion: despite the evident decrease in leprosy in the state, the most serious forms of the disease, which are related to higher levels of disability and transmission, showed little reduction.